Evidence of Tunable Fano Resonance in a Liquid Crystal‐Based Colloidal Metamaterial. Issue 11 (30th March 2020) - Bhardwaj, Amit; Sridurai, Vimala; Puthoor, Navas Meleth; Nair, Aswathi B.; Ahuja, Tripti; Nair, Geetha G.
Abstract: A colloidal metamaterial composite, realized by dispersing sub‐micrometer‐sized high refractive index dielectric resonators (selenium) in a nematic liquid crystal medium, exhibits electrically tunable Mie resonances in the optical regime. Darkfield hyperspectral imaging reveals that when the nematic liquid crystal (NLC) molecules reorient from the pristine planar state on application of an AC electric field, the scattered image from the particle splits into two, owing to the birefringence of the NLC medium. At higher voltages, a doughnut‐shaped scattering pattern is obtained, indicating the occurrence of Fano resonance. The analysis of the darkfield scattering spectra based on the "Multi‐pole Fano interference model" confirms the presence of Fano resonance arising due to the interference between the broad electric dipolar and narrow electric quadrupolar modes. With increasing voltage, the value of Fano parameter q decreases and approaches unity corresponding to an ideal Fano shape. Thus, the inherent optical anisotropy of the NLC medium and Fano coupling between the Mie resonant modes lead to highly reversible changes in the far‐field scattering pattern with potential applications in refractive index sensing, wave‐guiding, etc. Abstract : A liquid crystal (LC)‐based metamaterial consisting of selenium microspheres exhibits tunable Fano resonance due to interference between electric dipolar and quadrupolar resonant modes in the optical regime. The electric field‐driven states show novel features such as split (owing to birefringence of the LC) and doughnut‐shaped scattering images in darkfield hyperspectral imaging. The Mie theory and finite element method simulations validate the findings.